2018
DOI: 10.21873/anticanres.12631
|View full text |Cite
|
Sign up to set email alerts
|

No Deterioration in Clinical Outcomes of Carbon Ion Radiotherapy for Sarcopenia Patients with Hepatocellular Carcinoma

Abstract: Abstract. Background/Aim: The relationship between sarcopenia and prognosis in carbon ion radiotherapy (C-ion RT) for hepatocellular carcinoma (HCC) has not yet been reported 66% and 77%, respectively (p=0.51) . Conclusion: Sarcopenia was not a prognostic factor for patients with HCC treated with C-ion RT, which was effective in HCC patients with sarcopenia without worsening the OS.The number of elderly patients with age-related loss of skeletal muscle mass (primary sarcopenia) has been on the rise in recent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…35 In this study, five of nine patients died of HCC, suggesting that the survival outcome was worse than that reported in other studies of C-ion RT for HCC.17, 36,37 This is probably because this study RT can provide excellent LC probability even for large tumors. 38,39 Collectively, our findings support that C-ion RT is a promising effective alternative therapy in patients with HCCCL in whom surgery can be challenging.…”
Section: Hepatology Researchsupporting
confidence: 69%
“…35 In this study, five of nine patients died of HCC, suggesting that the survival outcome was worse than that reported in other studies of C-ion RT for HCC.17, 36,37 This is probably because this study RT can provide excellent LC probability even for large tumors. 38,39 Collectively, our findings support that C-ion RT is a promising effective alternative therapy in patients with HCCCL in whom surgery can be challenging.…”
Section: Hepatology Researchsupporting
confidence: 69%
“…In recent years, charged particle therapy (CPT), a relatively novel, non-invasive and promising treatment option, has made remarkable progress in the treatment of HCC [3638]. Protons (proton beam therapy, PBT) and carbon ions (carbon ion therapy, CIT) are the most commonly used particles of CPT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies involving C-ion RT have shown encouraging clinical outcomes that indicate C-ion RT would be an alternative treatment option for patients for which surgery or RFA are not viable options [1217, 29]. Shibuya et al demonstrated clinical outcomes of C-ion RT for HCC in a multi-institutional retrospective analysis and reported 2-year OS and LC rates for single HCC of 84 and 87%, respectively [13].…”
Section: Discussionmentioning
confidence: 99%